Annual cost of hospitalization, inpatient rehabilitation, and sick leave for head and neck cancers in Germany - Klussmann JP; Schädlich PK; Chen X; Rémy V (Dove Medical Press, 2013)
Jens P Klussmann,1 Peter K Schädlich,2 Xiaoyu Chen,2 Vanessa Rémy31Department of Otorhinolaryngology, Head and Neck Surgery, University of Giessen, Giessen, 2IGES Institut, Berlin, Germany; 3Sanofi Pasteur MSD, Lyon, FranceBackground: Data on the economic burden of head and neck cancers (HNCs) in Germany is scarce. About 16%–28% of these cancers are associated with human papillomavirus (HPV) infection. Therefore, the study reported here aimed to assess the annual costs of HPV-related HNCs incurred by hospitalization, inpatient rehabilitation, and sick leave in Germany in 2008.Methods: A cross-sectional retrospective analysis of five German databases covering hospital treatment, inpatient rehabilitation, and sick leave in 2008 was performed. All hospital, inpatient rehabilitation, and sick leave cases due to HNCs in 2008 were analyzed. Associated numbers of HNC hospitalizations, health care resource use, and costs were identified and extracted using the International Classification of Diseases, tenth revision (ICD-10; World Health Organization, Geneva, 1990) codes C01–C06, C09–C14, and C32 as the main diagnoses. Resources were valued with German official prices in 2008 euros (€). The annual costs of HPV-related HNCs were estimated based on the percentage of HNCs likely to be attributable to HPV infection.Results: In 2008, there were 63,857 hospitalizations, 4898 inpatient rehabilitations, and 17,494 sick leaves due to HNCs, representing costs of €365.78 million. The estimated annual costs associated with HPV-related HNCs were €78.22 million, mainly attributed to males (80%). Direct costs accounted for 84% (80% for hospital treatment, 4% for inpatient rehabilitation) and indirect costs due to sick leave accounted for 16% of HPV-related HNC costs.Conclusion: The economic burden of HPV-related HNCs in Germany in 2008 has been underestimated, since costs incurred by outpatient management, outpatient chemotherapy, long-term care, premature retirement, and premature death were not included. However, as far as we are aware, this study is the first analysis to investigate the economic burden of HNCs in Germany. The estimated annual costs of HPV-related HNCs contribute to a significant economic burden in Germany and should be considered when assessing the health and economic benefits of HPV vaccination in both sexes.Keywords: human papillomavirus, cost of illness, HPV, economic burden, 2008